The Influence of Brand Image, Brand Awareness and Consumer Attitude on the Purchase Decision of Non-Alcoholic Beers With Purchase Interest as a Mediator Variable - Kharismatyawati, Widhi; Janfry Sihite (Dinasti Publisher, 2023)
Beer is always associated with something negatively because it causes drunkenness and is closely related to night entertainment. Moreover, the majority of Indonesian people are Muslim and prohibit alcoholic beverages. Even though Bintang Bir has issued a zero-alcohol product with free alcohol content, Indonesian people still perceive that the brand is closely related to Khamr. However, Indonesia lawful institution has rules not to process halal certification for tasyabbuh products or similar products forbidden in Islam. This study aimed to examine and analyze the effect of brand image, brand awareness and consumer attitude on purchasing decisions for Bintang Zero Alcohol beer with purchase intention as a mediating variable. The sample in the study required a minimum of 280 samples using purposive sampling, taking into account specific criteria, and the final sample obtained was 282 consumers of Bintang Zero Alcohol drink. The results of this study state that brand image, brand awareness, and consumer attitudes encourage the achievement of buying interest. Brand image, awareness, consumer attitude, and buying interest drive the purchase decision. Purchase intention is a mediating variable in the relationship between brand image, brand awareness, and consumer attitudes towards purchasing decisions.